Focusing of positron bunch when moving in electron bunch wakefield in the dielectric waveguide filled with plasma - Sotnikov, G.V.; Knyazev, R.R.; Markov, P.I.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2021)
The results of numerical PIC-simulation of focusing accelerated (test) positron and drive electron bunches in the dielectric waveguide filled with radially heterogeneous plasma with the vacuum channel are given in the paper. The wakefield was excited by electron bunch in quartz dielectric tube, inserted into cylindrical metal waveguide. The internal area of dielectric tube has been filled with plasma different transverse density profiles, heterogeneous on radius, with the vacuum channel along waveguide axis. Plasma density for all studied cases was so low that plasma frequency was less, than the frequency of the main dielectric mode. Results of numerical PIC simulation have shown that possibility of simultaneous acceleration and focusing of the test positron bunch are possible in the wakefield. The best acceleration happens in case of plasma absence, however at that there is no focusing of test positron bunch.